Oxidation of gram-negative cell-wall proxy with OH radicals - kinetics and mechanism for water industry II - Professor Martin King; Dr Rebecca Welbourn; Mr Tobias Robson; Dr Luke Clifton; Dr Thomas Arnold; Dr Katherine Thompson (ISIS Facility, 2019)
Hydroxyl radicals may be used as disinfection agent in the advanced oxidation processes or tertiary treatment of waste and occasionally drinking water. We very recently oxidised a gram negative bacterial cell wall proxy at the liquid-solid interface with aqueous hydroxyl radical, the experiment (RB1820244) was a complete success and is being written up as a letter for publication. Our previous exploratory work, demonstrated the polysaccharides are an effective layer to resist oxidative attack, but did not characterise the structure of the film during oxidation – we propose to study the oxidised film with multiple contrasts and angles to determine if the oxidised film ‘holes’ or ‘thins’ and can be completely removed or not. The proposal is a collaboration between two teams with expertise in bacterial cell wall proxies and oxidation kinetics. It supports a joint ISIS/DLS funded student.
Keywords: STFC ISIS Neutron and Muon Data